2020
DOI: 10.15408/kauniyah.v13i1.14810
|View full text |Cite
|
Sign up to set email alerts
|

Kadar Mangiferin Pada Lima Kultivar Pucuk Daun Mangga (Mangifera indica L.)

Abstract: AbstrakPemanfaatan pucuk daun mangga (Mangifera indica L.) oleh masyarakat menjadi lalapan dan dipercaya berkhasiat sebagai obat tradisional. Hal ini merupakan suatu proses kearifan lokal berdasarkan pengalaman empiris orang-orang terdahulu yang kemudian dijadikan kajian studi ilmiah, yaitu etnobotani. Kajian studi etnobotani termasuk pemanfaatan pucuk daun mangga sebagai lalapan masih jarang dilakukan. Penelitian ini bertujuan untuk mengetahui senyawa bioaktif termasuk mangiferin yang terkandung dalam lima ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
2
0
5
Order By: Relevance
“…According to Medina Ramírez et al ( 2016), the highest mangiferin in mango plants is found in young mango leaves or mango leaf shoots. It is supported by Cahyanto et al (2020) which stated that the highest mangiferin was found in mango leaf shoot extract of Arumanis cultivar with percentage 20.83%. The high of mangiferin can describe antioxidants in mango leaf shoot extract which has a role in increasing cell regeneration in wound healing process.…”
Section: Introductionmentioning
confidence: 69%
“…According to Medina Ramírez et al ( 2016), the highest mangiferin in mango plants is found in young mango leaves or mango leaf shoots. It is supported by Cahyanto et al (2020) which stated that the highest mangiferin was found in mango leaf shoot extract of Arumanis cultivar with percentage 20.83%. The high of mangiferin can describe antioxidants in mango leaf shoot extract which has a role in increasing cell regeneration in wound healing process.…”
Section: Introductionmentioning
confidence: 69%
“…Daun mangga arum manis merupakan varietas mangga yang paling banyak di Indonesia sehingga mudah ditemukan serta memiliki kandungan metabolit sekunder dan mangiferin yang lebih tinggi dibandingkan varietas Mangifera indica L. lainnya. 14,23 Berdasarkan penjelasan diatas, peneliti tertarik untuk meneliti efektivitas ekstrak daun mangga arum manis (Mangifera indica L.) dalam hal menghambat pertumbuhan Candida albicans pada plat resin akrilik heat-cured dengan konsentrasi 65%, 75%, 85%, dan 100% yang mengacu pada konsentrasi efektif antijamur ekstrak daun mangga bacang (konsentrasi 50% dan 100%) pada penelitian terdahulu oleh Arifin et al 21 Hal yang membedakan dengan penelitian terdahulu ialah metode uji antijamur, jenis pelarut, media, dan jenis daun mangga yang digunakan.…”
Section: Pendahuluanunclassified
“…Thus, the consumption of natural products derived from plants is believed to improve health. In several Southeast Asian countries, young Mangifera indica leaves are commonly eaten fresh as a salad or side dish (Cahyanto et al, 2020). This habit has become a local tradition.…”
Section: Pancreatic Lipase Inhibitory Effectmentioning
confidence: 99%